2013
DOI: 10.3762/bjoc.9.238
|View full text |Cite
|
Sign up to set email alerts
|

Flow synthesis of a versatile fructosamine mimic and quenching studies of a fructose transport probe

Abstract: SummaryWe describe the synthesis of 1-amino-2,5-anhydro-D-mannose (“mannitolamine”), a key intermediate to the 7-nitro-1,2,3-benzadiazole conjugate (NBDM), using commercially available fluidic devices to increase the throughput. The approach is the first example of a flow-based Tiffeneau–Demjanov rearrangement. Performing this step in flow enables a ~64-fold throughput enhancement relative to batch. The flow process enables the synthesis to be accomplished three times faster than the comparable batch route. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Plutschack et al [57] applied the TD in a flow-based approach to contract a six-membered ring to a five-membered ring (Scheme 19). This was achieved using an acidic resin in which the educt, glucosamine hydrochloride, was passed over.…”
Section: Scheme 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Plutschack et al [57] applied the TD in a flow-based approach to contract a six-membered ring to a five-membered ring (Scheme 19). This was achieved using an acidic resin in which the educt, glucosamine hydrochloride, was passed over.…”
Section: Scheme 16mentioning
confidence: 99%
“…Comparing these results with the previously used batch production, a ~ 64-fold increase in the throughput rate and a decrease in reaction time from 3 days to 1 day was observed. This modification of the TD helps to shift the paradigm of synthesis away from the one-pot-approaches to dynamic flow-approaches, which are not only easier to control, but can also lead to shorter reaction time due to higher throughput [57].…”
Section: Scheme 16mentioning
confidence: 99%
“…The next generation of radiotracer probes was derived from 2,5‐anhydro‐ d ‐mannitol, on the basis of its high affinity towards Glut 5. 1‐[ 18 F]fluoro‐1‐deoxy‐2,5‐anhydro‐ d ‐mannitol ( 13 , Scheme ) was tested for PET imaging of breast tumor in rabbits by Sun and co‐workers . The results showed that the probe is taken up more avidly by the tumor than by normal cells but is rapidly excreted.…”
Section: Biochemical and Biomedical Glut Agentsmentioning
confidence: 99%
“…[23][24][25]28] Scheme5.Glucose-and fructose-based PET imagingprobes. [30,34,36,[39][40][41] ChemBioChem 2017, 18,1774 -1788 www.chembiochem.org Fructose-transport-targeting probesa ttracted attention due to the apparent connectionb etween the expression of fructose transporterG lut 5a nd cancerd evelopment, progression, and metastasis. [5] Designedb yM aeda and co-workers, [38] 1-[ 18 F]fluoro-1-deoxy-d-fructose (1-FDF, 11,S cheme 5) was the first fructose derivativetested as at racer for targeting Glut 5i n cancers.S ynthesized in two steps from 2,3,4,5-di-O-isopropylidene-1-O-(trifluoromethanesulfonyl)-d-fructose, 1-[ 18 F]fluoro-1deoxy-d-fructose was tested in mouse and rat tumor xenografts and showed rapid clearance through kidney and liver.…”
Section: Gluts and Diagnostic Probesmentioning
confidence: 99%
“…GLUT4 has been found to have links with insulin resistance and diabetes and has been a potential therapeutic target [26]. [18][19][20], because GLUT transporters being antiporter take up and excrete carbohydrates, but not their phosphorylated analogs [21]. As a result, sugar transport is loosely coupled to phosphorylation, so that a high rate of sugar accumulation is maintained without requiring a reduction in the intracellular sugar concentration.…”
Section: Gluts: Classification and Expressionmentioning
confidence: 99%